Synthesis and Characterization of Ferrofluid-Chitosan-Au Nanoparticles as Brachytherapy Agent Candidate - Muflikhah Muflikhah; Ahmad Marzuki Ramadhan; Maria Christina Prihatiningsih; Mujamilah Mujamilah; Aloma Karo Karo (Indonesian Journal of Chemistry, 2021)
Brachytherapy is expected to be a solution to the side effect of other cancer therapy methods. This study aims to synthesize ferrofluids (FF)-Chitosan-Au (so-called cold synthesis) as the initial step before using 198Au that is expected to be a targeted and controllable brachytherapy agent. In this research, the preparation of FF-Chitosan was done by the co-precipitation method. Furthermore, FF-Chitosan-Au was produced via self-assembly by the adsorption method. The adsorption followed the Langmuir model with a maximum capacity of 30.24 mg Au/g FF-Chitosan. The X-Ray Diffractometion (XRD) of FF-Chitosan-Au confirms the existence of Au. Particle Size Analyzer (PSA) indicates FF-Chitosan-Au has an average size of 82.93 nm with a polydispersity index of 0.175. Morphological and distribution analysis of nanoparticles using Scanning Electron Microscope (SEM) shows that nanoparticles have a homogenous spherical shape. Vibrating Sample Magnetometer (VSM) measurement confirms the superparamagnetic properties of FF-Chitosan and FF-Chitosan-Au with a saturated magnetization of 80.48 and 74.52 emu/g, respectively. The overall results are associated with biomedical requirements, such as high saturation magnetization and good polydispersity. The synthesis can also be applied to produce FF-Chitosan-198Au that has great potential as a brachytherapy agent, which will reduce the nuclear waste and potential danger of radiation received by workers during synthesis.